Hur mycket naturbetesmarker har vi idag? - Palmgren, Emma (2010)
To reach objectives within EU’s Habitatdirective and the national environmental objectives, more information about semi-natural pastures is required. The expression semi-natural pasture is used for pastures that during the latest time are uncultivated and unfertilized. Semi-natural pastures are important in many respects for example to conserve the biodiversity and for our cultural history. The aim of my study was to compile and calculate the area of semi-natural pastures by use existing sources of information. The most used sources for reporting and decisions are datasets from Swedish Board of Agriculture; the database TUVA and the Swedish block database. Due to the difficulty to locate and registry pastures in one database it´s likely that some of the pastures are missing. Therefore I used sample inventories to calculate or estimate the area of semi-natural pastures. The estimations for the total area of semi-natural pastures in Sweden are between 390 000 and 590 000 ha, depending on which inventory is used but also which land use that is defined as semi-natural pasture. When the results were compared with data from TUVA and the block database it turned out that the estimations from the sample inventories were significantly higher. Based on these analyses it was concluded that the amount of semi-natural pastures in Sweden is about 510 000 ha. To investigate the proportion of semi-natural pastures registered in TUVA and in the block database some spatial analyses were done. Plots from a sample inventory were compared towards the databases. These analyses aimed to study the amounts of semi-cultivated that are missing in the databases used for reporting and decisions. The proportion of registered semi-cultivated pastures differs quite a lot among regions within Sweden. Seen all over the country, approximately 30 % of the semi-natural pastures are not registered in either TUVA or the block database. Analyses also indicate that TUVA only consist information about 25-30 % of the semi-cultivated pastures. Even if the quality of pastures outside TUVA and the block database is relatively unknown, they need to be investigated before they disappear. These results are important to highlight since the content in the databases have sense for the quantity of economic support that is allocated to meadows and pastures. It is possible that more registrations could contribute to an increase of the economic support.